Expression level of sarah, a homolog of DSCR1, is critical for ovulation and female courtship behavior in Drosophila melanogaster. - Ejima, A.; Tsuda, M.; Takeo, S.; Ishii, K.; Matsuo, T.; Aigaki, T. (Genetics, 2004)
To better understand the genetic bases of postmating responses in Drosophila melanogaster females, we screened a collection of PGS insertion lines and identified two insertions in sarah (sra), whose misexpression in the nervous system induced high levels of ovulation in virgins. The gene sra encodes a protein similar to human Down syndrome critical region 1 (DSCR1). The ovulation phenotype was reproduced in transgenic virgins expressing UAS-sra in the nervous system. The flies also extruded the ovipositor toward courting males as seen in wild-type mated females, supporting the notion that ovulation and behavioral patterns are physiologically coupled. The sra insertions were found to be hypomorphic alleles with reduced expression levels. Females homozygous for these alleles show: (1) spontaneous ovulation in virgins, (2) sterility with impaired meiotic progression, and (3) compromised postmating responses with lower ovulation level, higher remating rate, and shorter period for restoration of receptivity. No obvious defects were observed in the homozygous males. The gene sra is predominantly expressed in oocytes, nurse cells, and the nervous system. Taken together, these results indicate that the expression level of sra is critical for ovulation and female courtship behavior, including their postmating changes.